O PROBLEMA DOS CUSTOS DA IMPLEMENTAÇO DOS DIREITOS HUMANOS E FUNDAMENTAIS NA CONSTITUIÇO BRASILEIRA (CIPEEX, 2022)
&NBSP;THE STUDY'S GENERAL OBJECTIVE IS TO ANALYZE HUMAN AND FUNDAMENTAL RIGHTS AND THEIR EFFECTIVENESS IN BRAZIL, AND THEN VERIFY THE ARGUMENT BROUGHT BY THE STATE REGARDING THE COSTS OF IMPLEMENTING FUNDAMENTAL RIGHTS.THE SPECIFIC OBJECTIVE IS TO WORK THE INSTITUTES INDIVIDUALLY SO THAT THE GENERAL OBJECTIVE IS ACHIEVED. AND DEMONSTRATE THAT ECONOMIC DEVELOPMENT IN THE SOCIAL RULE OF LAW IS ONLY ACHIEVED WITH THE PROPER DISTRIBUTION OF ESSENTIAL FUNDAMENTAL RIGHTS.THE WORK IS JUSTIFIED IN VIEW OF THE HIGH JUDICIAL DEMAND DEMANDING THE IMPLEMENTATION OF FUNDAMENTAL RIGHTS, SUCH AS HEALTH, EDUCATION, DECENT WORK, AMONG OTHERS. AND, THEREFORE, IT IS NECESSARY TO VERIFY WHETHER THE STATE MUST PROVIDE THESE RIGHTS GUARANTEED BY THE CONSTITUTION AND BY INTERNATIONAL TREATIES OR NOT.TO DEVELOP THE WORK, BIBLIOGRAPHICAL RESEARCH WAS USED, SURVEYING THE MAIN CONCEPTS RELEVANT TO THE TOPIC WITH SCHOLARS AND RESEARCHERS. AND, AS A RESULT, IT IS EXPECTED TO UNDERSTAND THE ARGUMENTS USED BY THE STATE AND THE REASONS FOR NOT ACCEPTING ITS ARGUMENTS OF FINANCIAL DIFFICULTY TO IMPLEMENT THE RIGHTS.